The Class of Homothetic Isoquant Production Functions: Programming Revisited - Clemhout, B. S. (Review of Economic Studies, 1970)
Journal Article The Class of Homothetic Isoquant Production Functions: Programming Revisited Get access Berkeley S. Clemhout Berkeley S. Clemhout University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 2, April 1970, Pages 302–303, https://doi.org/10.2307/2296424 Published: 01 April 1970